Comparison of Sensitivity and Specificity of Alvarado Score and Tzanakis Score in Enforcement of Acute Appendicitis Diagnosis - Tsany Tsamara Amnedya; Sony Wijaya (Syntax Corporation Indonesia, 2023)
Appendicitis is inflammation of the appendix that occurs due to fecalitis, fibrosis, foreign bodies, or neoplasia. Based on WHO data in 2014, appendicitis is ranked 8th as the cause of death and is expected to continue to increase in the upcoming years. In the Southeast Asian region, the incidence of acute appendicitis is found in almost all Southeast Asian countries. Indonesia with a prevalence of 0.05% ranks first as the country with the highest incidence of acute appendicitis. Appendicitis has clinical manifestations in the form of visceral pain that is felt around the umbilicus, which within a few hours will move to the right under McBurney's point, fever, nausea, and vomiting as the result of infection. Difficulties in diagnosing acute appendicitis arise especially in pediatric patients, the elderly, and women of reproductive age because the symptoms they cause often overlap with other conditions.